2022
DOI: 10.2196/31747
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Virtual Reality Puzzle Game to Decrease Food Intake: Randomized Controlled Trial

Abstract: Background Virtual reality (VR) has gained popularity in daily life, and VR food cues seem to elicit food cravings, similar to real food cues. However, little is known about the impact of VR food cues on actual food intake. Objective In real life (RL), exposure to food cues in a situation in which the desire to eat food interferes with the completion of a food-related task reduces the subsequent food intake (ie, the pre-exposure effect). In this study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Regarding physiological responses, increases in skin conductance , heart rate (García- Rodríguez et al, 2013;Thompson-Lake et al, 2015), pre-frontal cortex activity (Lee et al, 2005), posterior EEG alpha power (Tamburin et al, 2021), and ocular fixations (Gamito et al, 2011;Liu, Stamos, Dewitte, van Berlo, & van der Laan, 2022) were found in cigarette smokers in response to virtual nicotine cue exposure.…”
Section: Assessment Studiesmentioning
confidence: 99%
“…Regarding physiological responses, increases in skin conductance , heart rate (García- Rodríguez et al, 2013;Thompson-Lake et al, 2015), pre-frontal cortex activity (Lee et al, 2005), posterior EEG alpha power (Tamburin et al, 2021), and ocular fixations (Gamito et al, 2011;Liu, Stamos, Dewitte, van Berlo, & van der Laan, 2022) were found in cigarette smokers in response to virtual nicotine cue exposure.…”
Section: Assessment Studiesmentioning
confidence: 99%